The unfamiliar garden - Percy, Benjamin (Percy, Benjamin. Comet cycle., 2022)
"From award-winning author Benjamin Percy comes the second novel in his grippingly original sci-fi series, The Comet Cycle, in which a passing comet has caused irreversible change to the growth of fungi, spawning a dangerous, invasive species in the Pacific Northwest that threatens to control the lives of humans and animals alike"--